A transient outward potassium current activator recapitulates the electrocardiographic manifestations of Brugada syndrome - Calloe, Kirstine (Oxford University Press, 2009)
AIMS: Transient outward potassium current (I(to)) is thought to be central to the pathogenesis of the Brugada syndrome (BrS). However, an I((to)) activator has not been available with which to validate this hypothesis. Here, we provide a direct test of the hypothesis using a novel I(to) activator, NS5806. METHODS AND RESULTS: Isolated canine ventricular myocytes and coronary-perfused wedge preparations were used. Whole-cell patch-clamp studies showed that NS5806 (10 µM) increased peak I(to) at +40 mV by 79 ± 4% (24.5 ± 2.2 to 43.6 ± 3.4 pA/pF, n = 7) and slowed the time constant of inactivation from 12.6 ± 3.2 to 20.3 ± 2.9 ms (n = 7). The total charge carried by I(to) increased by 186% (from 363.9 ± 40.0 to 1042.0 ± 103.5 pA·ms/pF, n = 7). In ventricular wedge preparations, NS5806 increased phase 1 and notch amplitude of the action potential in the epicardium, but not in the endocardium, and accentuated the ECG J-wave, leading to the development of phase 2 re-entry and polymorphic ventricular tachycardia (n = 9). Although sodium and calcium channel blockers are capable of inducing BrS only in right ventricular (RV) wedge preparations, the I(to) activator was able to induce the phenotype in wedges from both ventricles. NS5806 induced BrS in 4/6 right and 2/10 left ventricular wedge preparations. CONCLUSION: The I(to) activator NS5806 recapitulates the electrographic and arrhythmic manifestation of BrS, providing evidence in support of its pivotal role in the genesis of the disease. Our findings also suggest that a genetic defect leading to a gain of function of I(to) could explain variants of BrS, in which ST-segment elevation or J-waves are evident in both right and left ECG leads.